ON DOUBLE WEIGHTED MEAN STATISTICAL CONVERGENCE - Kumar Raghuvanshi, Aditya; Singh, B.K.; Kumar, Ripendra (International Journal of Research -GRANTHAALAYAH, 2017)
In this paper, we have established some new theorems on double weighted mean statistical convergence of double sequences, which gives some new results and generalizes the some previous known results of Karakaya.